2019
DOI: 10.1136/ijgc-2018-000016
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer: screening and future directions

Abstract: Ovarian cancer carries a lifetime risk of approximately 2% for women and is the leading cause of death from any gynecologic malignancy. Currently, no screening program for ovarian cancer exists for the general population in the UK. This review focuses on the evidence surrounding the efficacy of current markers and discusses future improvements in screening for this disease. One-off cancer antigen 125 (CA125) measurements for detecting ovarian cancer have been well researched. However, studies have highlighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 30 publications
0
74
0
2
Order By: Relevance
“…The detection of serum tumor markers is a common detection method in the diagnosis of malignant tumors, because it is simple and inexpensive, and the samples are easy to collect. CA125 is still the most commonly used biomarker for the diagnosis and efficacy monitoring of OC, providing valuable information for the determination of the benign and malignant ovarian tumors (11). It has been reported that CA125 is elevated in the serum of most ovarian epithelial carcinoma, and continuous elevation of CA125 level indicates a relatively poor prognosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of serum tumor markers is a common detection method in the diagnosis of malignant tumors, because it is simple and inexpensive, and the samples are easy to collect. CA125 is still the most commonly used biomarker for the diagnosis and efficacy monitoring of OC, providing valuable information for the determination of the benign and malignant ovarian tumors (11). It has been reported that CA125 is elevated in the serum of most ovarian epithelial carcinoma, and continuous elevation of CA125 level indicates a relatively poor prognosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is the highest mortal gynecological malignant tumor, while the five-year survival rate has long been teetering at 30% [1]. Currently, the standard treatment for ovarian cancer is maximal cytoreductive surgery and platinum-based chemotherapy [2].…”
Section: Introductionmentioning
confidence: 99%
“… 2 In most cases, surgery and chemotherapy elicit an initial good response, which however is followed by relapse of chemoresistant clones that inevitably lead to death the patient. 3 , 4 The tumor microenvironment, with its unique composition in stromal- and immune cell-derived cytokines and of blood and lymphatic vessels that determine the availability of nutrients, growth factors and oxygen, plays a pivotal role in ovarian cancer cell metabolism and progression. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%